Maximizing quinoa production through a dual-purpose harvesting method - Ndunguru, Grato; Ayele, Addissu G.; Pathan, Safiullah (Frontiers in Plant Science, 2025)
This study introduces a novel dual-purpose quinoa production method, allowing the harvest of leafy greens first and grains later from the same plant, thereby enhancing overall production and economic returns. Four quinoa lines were evaluated under two treatments: (1) cut, where leafy greens were harvested four weeks after germination, and plants were subsequently allowed to mature, and (2) control, where plants were grown to full maturity without cutting. The study employed a randomized complete block design (RCBD) with three replications across three planting dates spaced at one-week intervals. Similar management practices were followed for both treatments and the date of planting. Results showed a significantly higher grain yield in cut plants (22.87g plant-1) compared to control plants (15.52g plant-1, p < 0.05). Quinoa line PI614927 yielded the highest in both cut and control treatments, with 29.15 and 18.33g plant-1, respectively. Grain yield was higher in the cut than the control on all three planting dates. The cut plants matured two days later than the control due to late branching and flowering. Shoot dry weight was significantly higher in cut plants (77.67g) than in the control (53.80g plant-1) due to a higher number of branches in cut plants (4–6 plant-1). In contrast, plant height and panicle length were higher in the control plant. The root dry weight was significantly higher in the cut (14.99g) than in the control (12.87g plant-1) plants. The two treatments showed no significant differences in 100-seed weight and root length. There was no significant difference in the nutritional compositions of quinoa grains between the treatments and dates of planting. This study has three benefits: harvesting leafy greens and higher grains, profound environmental benefits from using less water and fertilizer, one-time field preparation, and short duration (around 100 days). These research findings can accelerate quinoa leafy greens and grains production, contributing to food and nutritional security and sustainable alternative crop production, especially for small farmers.